Russian Culture as a Text: Dialogues with Time in the Work of Andrei Platonov and the Venedict Eropheev: Русская культура как текст: диалоги со временем в творчестве Андрея Платонова и Венедикта Ерофеева - Shemyakina, Olga; Gushchina, Dina (Przegląd Wschodnioeuropejski, 2020)
The authors trace the functioning and interaction of cultural paradigms that determine the time of a long duration. The article discusses some mechanisms of the influence of these paradigms on the modern literary process. The focus of the authors of the article is the study of the literary process by the example of the work of Andrey Platonov and Venedikt Yerofeyev. Analyzed are the prerequisites for changing the boundaries of the dialogue with different cultures, which have become a spiritual reflection of the world-systemic connections of the modern world. The authors trace how spatial, temporal representations and ritual practices are reanimated in the imaginative world of writers, and also study the mechanisms that give rise to deep traditional layers of consciousness, such as trauma, disintegration and drama.